Optimization of heat exchangers of refrigeration machines by entropy generation minimization method - Морозюк, Лариса Ивановна (Eastern-European Journal of Enterprise Technologies, 2015)
The development of new and modernization of serial heat exchangers are inextricably linked with the identification of their effectiveness. The effectiveness of the heat exchanger as part of the refrigeration machine was analyzed from three perspectives: economic, energy and thermodynamic using specific criteria. Considering modern thermodynamic analysis methods, which are based on determining irreversible losses in the processes of refrigeration machines, the entropy generation minimization method for analyzing heat exchangers was proposed. The choice of the method has provided an analysis of the processes in a particular heat exchanger of the refrigeration machine irrelatively of other elements, and analysis of one flow in the heat exchanger, which determines the energy side of the operation. It is shown on a particular example of the water condenser that using the entropy generation minimization method eliminates complex and unproductive calculations, providing the designer with the tools, the action principle of which is based on scientific and independent thermodynamic laws. The characteristics that meet the entropy generation minimum, ensure power-saving mode at the design stage and in a subsequent operation. The method is an alternative to a feasibility study and preferred for refrigeration machines due to the absence of cost indexes.